2020
DOI: 10.1088/1757-899x/671/1/012076
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fibre on the mechanical properties of aerated concrete

Abstract: Aerated concrete (AC) is lightweight concrete in which air voids are captured in the mortar by means of the addition of an aerating agent to meet specific requirements of density and strength. Aerated concrete displays brittle failure in tension, however, and thus an alternative solution to make the concrete more ductile and reduce the problem of cracking is to add steel bars or steel fibre. The aim of this study is thus to investigate the effect of steel fibres on the compressive strength, flexural strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The flexural ultimate strength for a thin-section beam was assessed with a third point loading (TPL) test [ 12 , 13 , 14 , 15 , 16 ]. The constant displacement rate used in this experiment was 2 mm × min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexural ultimate strength for a thin-section beam was assessed with a third point loading (TPL) test [ 12 , 13 , 14 , 15 , 16 ]. The constant displacement rate used in this experiment was 2 mm × min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Aldikheeli et al [ 12 ] investigated the effect of the inclusion of hooked-end steel fibers on the density of cement mortar using two diameters and lengths. It was reported that the dry densities of the composites exceeded that of their conventional counterpart, increasing to ~5.4% at a concentration of steel fibers of 1.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Short fiber length (i.e., 5 mm) in composite samples resulted in higher flexural strength which primary control the microcrack propagation [73]. Furthermore, short fibers also increase the number of fibers which bind closely in the composite samples and therefore increase the flexural strength [74]. Flexural strength corresponding to 10-15 mm fiber length in the polyester composites is lesser compared that of 20 mm fiber length specimens.…”
Section: Flexural Testmentioning
confidence: 98%
“…Fibers 2022, 10, x FOR PEER REVIEW 8 of 16 [74]. Flexural strength corresponding to 10-15 mm fiber length in the polyester composites is lesser compared that of 20 mm fiber length specimens.…”
Section: Flexural Testmentioning
confidence: 99%
“…A lot of research has been performed to explore the effect of fibres on the mechanical properties of concrete [15][16][17]. Naaman and Reinhardt [18] reported that adding a little fraction of short Torex fibres, which are engineered to achieve optimal properties in the order of 0.5% to 1% by volume, in concrete could enhance the toughness in the post-cracking response by bridging across the cracks.…”
Section: Introductionmentioning
confidence: 99%